Perancangan Sistem Pendeteksi Jaringan Seluler Di Bawah Jaringan Teganggan Tinggi Sutet Berbasis IOT - Kemal Farouq Mauladi; Nurul Fuad; Affan Bachri (Jurnal Teknika, 2019)
Internet Of Things (IoT) Is A Concept Where Internet Connectivity Can Exchange Information With Each Other With Things Around It. Many Predict That the Internet of Things (IoT) is “The Next Big Thing” in the World of Information Technology. System Testing Is Done In The Graha Indah District Of Lamongan Regency. Sensor Nodes Will Be Placed Near High Teget Sutet Network, Atmega 828 Microcontroller in this study as NodeMCU to be able to read data from sensors and convert the data obtained into the form of numbers that are easy to understand. Another function of the program is to send the data to the middleware every 50 seconds. Data retrieval every 60 minutes is intended to be able to get strong and weak GSM network signals that are close to the SUTET electricity network.